SIMULATION OF FLUID MOTION USING SMOOTH PARTICLE HYDRODYNAMIC METHOD - Nooreza, Kaisa
Virtual 2-dimensional fluid simulation can help in simulating fluids directly in various problems, such as fluid simulations for education, geological simulations for landslides, and so on. This thesis aims to simulate the behavior of three different types of fluids (water, coconut oil, and glycerin) in a 2D container and analyze how these three types of fluids behave under various conditions, including interactions with boundaries. This research was simulated using the Python programming language to simulate fluids and using the Wondershare Filmora X application to combine images. This research method uses the Smooth Particle Hydrodynamics method to simulate fluid in a 2-dimensional container with a total of 10,000 particles. This research uses the Smooth Particle Hydrodynamics method to help model fluids in particle form by deriving the force density field directly from the Navier-Stokes equations. The Navier-Stokes equations are used to find the acceleration and velocity of fluid particles by including external forces, internal forces and gravity through the Smooth Particle Hydrodynamics method. Acceleration and velocity will be validated due to wall collisions, collisions with boundaries and collisions between particles which cause changes in particle position and particle velocity. During visualization, the fluid velocity slows down over time due to attenuation caused by interactions between fellow particles, particles with boundaries and particles with walls. Here you can see the behavior of the fluid flowing from a higher place to a lower place, the fluid particles are shaped like a container, the surface of the fluid is shaped like a wave and in simulations with boundaries it is found that the fluid's ability to penetrate a gap is influenced by the size of the gap and the value of the viscosity. fluid dynamics.